Rationalizing the permeation of polar antibiotics into Gram-negative bacteria. (3rd February 2017) - Scorciapino, Mariano Andrea; Acosta-Gutierrez, Silvia; Benkerrou, Dehbia; D'Agostino, Tommaso; Malloci, Giuliano; Samanta, Susruta; Bodrenko, Igor; Ceccarelli, Matteo
Abstract: The increasing level of antibiotic resistance in Gram-negative bacteria, together with the lack of new potential drug scaffolds in the pipeline, make the problem of infectious diseases a global challenge for modern medicine. The main reason that Gram-negative bacteria are particularly challenging is the presence of an outer cell-protecting membrane, which is not present in Gram-positive species. Such an asymmetric bilayer is a highly effective barrier for polar molecules. Several protein systems are expressed in the outer membrane to control the internal concentration of both nutrients and noxious species, in particular: (i) water-filled channels that modulate the permeation of polar molecules and ions according to concentration gradients, and (ii) efflux pumps to actively expel toxic compounds. Thus, besides expressing specific enzymes for drugs degradation, Gram-negative bacteria can also resist by modulating the influx and efflux of antibiotics, keeping the internal concentration low. However, there are no direct and robust experimental methods capable of measuring the permeability of small molecules, thus severely limiting our knowledge of the molecular mechanisms that ultimately control the permeation of antibiotics through the outer membrane. This is the innovation gap to be filled for Gram-negative bacteria. This review is focused on the permeation of small molecules through porins, considered the main path for the entry of polar antibiotics into Gram-negative bacteria. A fundamental understanding of how these proteins are able to filter small molecules is a prerequisite to design/optimize antibacterials with improved permeation. The level of sophistication of modern molecular modeling algorithms and the advances in new computer hardware has made the simulation of such complex processes possible at the molecular level. In this work we aim to share our experience and perspectives in the context of a multidisciplinary extended collaboration within the IMI-Translocation consortium. The synergistic combination of structural data, in vitro assays and computer simulations has proven to give new insights towards the identification and description of physico–chemical properties modulating permeation. Once similar general rules are identified, we believe that the use of virtual screening techniques will be very helpful in searching for new molecular scaffolds with enhanced permeation, and that molecular modeling will be of fundamental assistance to the optimization stage.